The Effect of Psychoeducation on the Level of Postpartum Blues in Postpartum Mothers - Sasanti, Dewi Ari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Postpartum “blues” are defined as low mood and symptoms of mild depression that are temporary and self-limited. However, a diagnosis of postpartum blues can make a person vulnerable to postpartum depression or postpartum anxiety disorder. The aim of this research is to determine the effect of psychoeducation on the level of postpartum blues in postpartum mothers. This research is quantitative research using a pre-experimental design with a one-group pre-post test design type of research. The population in this study was postpartum/postpartum mothers on days 3-10. The research results show that the value of Asymp. Sig. (2-tailed) > 0.05, namely 0.841. The conclusion from this study is that there is no effect of psychoeducation on the level of postpartum blues in postpartum mothers.